Characterization of fluidized beds hydrodynamics by recurrence quantification analysis and wavelet transform. (March 2015) - Tahmasebpoor, Maryam; Zarghami, Reza; Sotudeh-Gharebagh, Rahmat; Mostoufi, Navid
Graphical abstract: Highlights: Hydrodynamic of gas–solid fluidized beds was studied by RQA and WT methods. Complex dynamic of fluidized beds were reduced to macro, meso and micro structures. Effect of gas velocity, particle size, settled height and bed diameter were studied. WT and RQA results were in consistence with each other at all conditions but scale. Entropy had more consistency with hydrodynamic in scale effect study. Abstract: This paper reports the development of nonlinear time series analysis technique based on recurrence quantification analysis (RQA) method to characterize the hydrodynamic of gas–solid fluidized beds and a comparison with the obtained results by wavelet transform (WT) analysis method is made. An experimental work has been carried out at varying conditions, e.g. bed diameter (5, 9, 15 cm ID), particle size (150, 300 and 600 μm), bed height at aspect ratios (1, 1.5 and 2) and superficial gas velocities (ranging 0.1–1.7 m/s). Both methods show that by using larger particles and higher aspect ratios, the contribution of macro structures increases in the system. By increasing the gas velocity, finer structures in the bed first lose their contribution and after passing a transition velocity (of about 0.3, 0.5 and 0.7 m/s for sands with mean diameters of 150, 300 and 600 μm respectively) their contribution increases again. While the frequency domain analysis is not sensitive to the effect of scale; the RQA method shows an increase in meso structure contribution by increasing of the bed diameter.